Erratum to: Biomass and nutrient accumulation by cover crops and upland rice grown in succession under no-tillage system as affected by nitrogen fertilizer rate (Journal of Crop Science and Biotechnology, (2020), 23, 2, (117-126), 10.1007/s12892-019-0288-0) - da Silva, Edson Cabral; Muraoka, Takashi; Bastos, Alefe Viana Souza; Franzini, Vinícius Ide; Buzetti, Salatiér [UNESP]; Soares, Frederico Antonio Loureiro; Teixeira, Marconi Batista; Bendassolli, José Alberto (Springer Nature, 2020)
Due to an unfortunate oversight the author’s name and affiliation have been given erroneously. It should be read: Vinícius Ide Franzini Embrapa Cocais, São Luiz MA, Brazil The authors apologies this mistake.